Branchial cleft carcinoma with cervical lymph node metastasis: a Case Report - Diao, Xiangyu; Han, Xuan; Zuo, Hongwei; Sun, Fenglin (Frontiers in Oncology, 2025)
Branchial cleft carcinoma is a rare malignant tumor originating from the epithelium of branchial cleft cysts, which are highly susceptible to misdiagnosis. There is a lack of systematic consensus on its lymph node metastasis pattern and standardized treatment protocol. We report a case of branchial cleft carcinoma with cervical lymph node metastasis and discuss its diagnostic criteria, clinicopathological features, lymph node metastatic characteristics, and treatment strategies. This case report supports the notion that branchial cleft carcinoma should be diagnosed according to Khafif’s criteria, and long-term follow-up is necessary to reduce the misdiagnosis rate. And treatment should be based on radical tumor resection combined with ipsilateral cervical lymph node dissection, and adjuvant radiotherapy is recommended for the presence of lymph node metastasis or locally invasive growth.